Analisis Kompetensi Pedagogis dan Profesional Guru PAUD di Abad-21 - Jalianti Rizkina Santoso; Tiara Magfirah Chalina; Wita Hazura; Rita Kurnia; Asfi Yanti WE (MAN 4 Kota Pekanbaru, 2025)
This study aims to analyze the pedagogical and professional competencies of early childhood teachers in 21st-century learning, particularly regarding the integration of technology and obstacles to creativity in the development of learning media. The study was conducted at Kindergarten “A” involving 10 teachers using qualitative descriptive methods through observation, semi-structured interviews, and documentation. The results showed that teachers had fairly good pedagogical and professional competencies, including in formulating activity objectives, preparing lesson plans, and delivering material in language appropriate for children. However, teachers' creativity in utilizing media was still limited, especially in the use of simple technology and modification of conventional media. Teachers tended to use the same tools repeatedly without innovation. The lack of training and professional support also hampered the development of creative media. This study recommends improving competence through training, mentoring, and strengthening institutional support to encourage learning innovations that are appropriate for children's development.